Effect of probiotics combined with immune checkpoint suppressors and chemotherapeutic agents on digestive system function, intestinal immunity and prognosis in patients with metastatic colorectal carcinoma: a quasi-experimental study - Xiaolei Wang; Yuxia Huang; Zhen Yang; Yang Yang; Fenfen Wei; Min Yan; Fanfan Li; Chenghao Wang (BMC Gastroenterology)
Abstract Objective An exploration of the influence of probiotics combined with immune checkpoint suppressors and chemotherapeutic agents on digestive system function, intestinal immunity and prognosis in patients with metastatic colorectal carcinoma. Methods This was a quasi-experimental study. During March 2019 to March 2020, 96 patients with metastatic colorectal carcinoma were arbitrarily classified into control group (n = 48) and intervention group (n = 48). The control group received only immune checkpoint inhibitors or chemotherapy, while the intervention group received immune checkpoint inhibitors or chemotherapy, plus probiotic therapy. Survival and complication rates after 6 months, 12 months and 2 years of treatment were calculated. Intestinal barrier function, immune function and quality of life were analyzed before and after treatment. Results Ninety-six patients were recorded at the follow-up demonstrating superior survival in the intervention group after 6 months, 12 months and 2 years of therapy. D-lactate and diamine oxidase (DAO) levels were elevated in the intervention group after treatment, with smaller elevations (P < 0.05). The levels of Bifidobacterium and Lactobacillus were remarkably higher in the intervention group after treatment compared to the control group prior to and following therapy (P < 0.05). The amount of Enterococcus and Escherichia coli in the intervention group after treatment was obviously lower compared to the pre-treatment and control groups (P < 0.05). CD3+, CD4+, and CD4+/CD8+ levels were found to be higher in the intervention group (P < 0.05), while CD8+ levels were reduced in the intervention group (P < 0.05). All dimensions of the QLQC-30 scale were higher in the intervention group (P < 0.05). The incidence of complications such as nausea and vomiting, loss of appetite, bloating and diarrhea was considerably reduced in the intervention group (P < 0.05). Conclusion Immune checkpoint suppressors combined with chemotherapeutic agents or probiotic regimens can obviously enhance the prognosis of patients with metastatic colorectal carcinoma. This combination therapeutic strategy can balance the imbalanced intestinal flora, improve intestinal function, and lessen the incidence of adverse events, so it is worthy of clinical application and can lessen the incidence of adverse reactions.